2007
DOI: 10.1088/0953-8984/20/03/035105
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear energy response of glass forming materials

Abstract: A theory for the nonlinear energy response of a system subjected to a heat bath is developed when the temperature of the heat bath is modulated sinusoidally. The theory is applied to a model glass forming system, where the landscape is assumed to have 20 basins and transition rates between basins obey a power law distribution. It is shown that the statistics of eigenvalues of the transition rate matrix, the glass transition temperature T g , the Vogel-Fulcher temperature T 0 and the crossover temperature T x c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…They showed that the anomalous behavior of the specific heat can be understood as a transition from the annealed average at high temperatures to the quenched average at low temperatures [13,14] and that the cooling rate dependence of the glass transition temperature can be accounted by the FEL frame work [15]. Recently, non-linear energy response of glass forming materials has been analyzed on the basis of the FEL picture and it is shown that the second order ac specific heat will exhibit characteristic behaviors related to the glass transition temperature and the Vogel-Fulcher temperature [16].…”
Section: Time-dependent Phenomenamentioning
confidence: 99%
“…They showed that the anomalous behavior of the specific heat can be understood as a transition from the annealed average at high temperatures to the quenched average at low temperatures [13,14] and that the cooling rate dependence of the glass transition temperature can be accounted by the FEL frame work [15]. Recently, non-linear energy response of glass forming materials has been analyzed on the basis of the FEL picture and it is shown that the second order ac specific heat will exhibit characteristic behaviors related to the glass transition temperature and the Vogel-Fulcher temperature [16].…”
Section: Time-dependent Phenomenamentioning
confidence: 99%
“…Therefore, the glass transition is usually recognized as a ''dynamic phase transition'' and T 0 is sometimes called an ''ideal glass transition temperature.'' There are many models to explain the divergence of the viscosity at T 0 , e.g., the entropy theories [1][2][3][4], free volume theories [5,6], free energy landscape scenarios [7][8][9][10][11], mode-coupling theories [12,13], and replica theory [14], etc. It is, of course, impossible to reach T 0 experimentally because the experimantal time scale is 10 6 s at longest.…”
mentioning
confidence: 99%
“…Notably that the linearization of the free energy (2) above T ∞ c leads to the harmonic (therefore, symmetric) potential with the second and the fourth eigenvalue given in equation ( 21). For the harmonic potential only the second eigenvalue contributes to the dynamic heat capacity, i.e., above T ∞ c in the bulk limit a = 0 and b = 0 in equation (17). However, the linearization below T ∞ c leads to the shifted harmonic (asymmetric) potential with the first eigenvalue 2α(T ∞ c − T ).…”
Section: Resultsmentioning
confidence: 99%
“…The static heat capacity (7) may be written in terms of a and b as C 0 = V 2 T 2 (a + b). The frequency-dependent heat capacity (17) indicates that generally for the symmetric (even) potential the timescales of the energy relaxation are defined by the even eigenvalues of the Fokker-Planck operator. For the harmonic potential only the second eigenvalue of the appropriate Fokker-Planck operator contributes to the relaxation process [14].…”
Section: Dynamic Heat Capacitymentioning
confidence: 99%
See 1 more Smart Citation